Conductive Metal–Organic Frameworks with Extra Metallic Sites as an Efficient Electrocatalyst for the Hydrogen Evolution Reaction - Hao Huang; Yue Zhao; Yimin Bai; Fumin Li; Ying Zhang; Yu Chen (Advanced Science, 2020)
Abstract The 2D conductive metal–organic frameworks (MOFs) are expected to be an ideal electrocatalyst due to their high utilization of metal atoms. Exploring a new conjugated ligand with extra active metallic center can further boost the structural advantages of conductive MOFs. In this work, hexaiminohexaazatrinaphthalene (HAHATN) is employed as a conjugated ligand to construct bimetallic sited conductive MOFs (M23(M13∙HAHATN)2) with an extra M–N2 moiety. Density functional theory (DFT) calculations demonstrate that the 2D conjugated framework renders M23(M13∙HAHATN)2 a high electric conductivity with narrow bandgap (0.19 eV) for electron transfer and a favorable in‐plane porous structure (2.7 nm) for mass transfer. Moreover, the metal atom at the extra M–N2 moiety has a higher unsaturation degree than that at M–N4 linkage, resulting in a stronger ability to donate electrons for enhancing electroactivity. These characteristics endow the new conductive MOFs with an enhanced electroactivity for hydrogen evolution reaction (HER) electrocatalysis. Among the series of M23(M13∙HAHATN)2 MOF, Ni3(Ni3∙HAHATN)2 nanosheets with the optimal structure exhibit a small overpotential of 115 mV at 10 mA cm−2, low Tafel slope of (45.6 mV dec−1), and promising electrocatalytic stability for HER. This work provides an effective strategy for designing conductive MOFs with a favorable structure for electrocatalysis.